O processo de somatização: Conceitos, avaliação e tratamento - Manuel João Quartilho (Ciências da Saúde, 2016)
Widely acknowledged as a relevant public health problem, linked to personal and interpersonal suffering, somatization is still an unresolved problem by medicine. Perhaps because it remains on its margins and asks for solutions that medicine can't offer, among other reasons. It means a clinical region largely ignored or devalued with the fatalistic presumption that the patients, who "are not ill", have to live with the symptomatic pattern that characterizes their behavior. This way, somatization arises as a recurrent motive for non-satisfaction for the patient and also as a frustrating experience for the doctor, given the difficulties that characterize their relationship and the usual non-efficacy of therapeutic interventions. The tacit silence of somatization in clinical practice is broken everyday by this discontent noise, both in primary care and in the general hospital. It is a silence mainly nourished by a most conventional biomedical persuasion, claiming that the patients do have nothing wrong with them. One of the main assumptions of this book defends that the patients have comprehensive and legitimate reasons, in biographical, social and cultural contexts so many times strange to the conventional clinical evaluation, to recur to the somatic metaphor.